Evaluación de tres bioinsecticidas en el control de spodoptera frugiperda J.E. SMITH en zea mays l. hibrido dekalb .. 7088 en Chao - La Libertad - Flores Cubas, Gilberto (2015)
The research entitled "Evaluation of three bio-insecticides to control Spodoptera.ft·ugiperda J.E. Smith Dekalb Hybrid Zea mays L. Chao-7088- Liberty ". It was held at Santa Teresita fann in the sector La Fortuna belonging to Buena vista district Chao, Vim Province, La Libertad Department since June 6, 2013 until December 4, 2013; having as objectives: T o evaluate three bioinsecticides to control Spodoptera frugiperda J. E. Smith in Zea mays L. hybrid DEKALB - 7088 Chao - La Libertad. Determine which of the three bioinsecticides present a greater control of Spodoptera frugiperda J.E. Smith in Zea mays L hybrid DEKALB -7088 Chao. Tdentify the beneficia] insect population after application ofbioinsecticides for the control of Spodopteraji·ugiperda J.E. Smith inZea mays L. hybridDEKALB -7088 Chao. The methodology used was Complete block design with three replications randomly, which consisted of three bio-insecticides Tracer 120 CS dose 60 ml/ cyl, Xentari WDG was used. Dose of 350 g 1 cyl and castor seed extract 1 O 1/ cyl anda control based insecticides Dethomil Troy 4 EC + 90 PS at the dos e of 300 ml and 100 g 1 cyl. respectively. Regarding evaluation of the three bioinsecticides in controlling Spodopetra frugiperda J. E. is highly significant, statistically signi:ficant differences in the characteristics evaluated both in the percentage of incidence, on the percentage of leaf area affected intensity and mean number of larvae per plant found; Tt·acer 120 se doce of 60 ml/cyl. always present average lower in these traits assessed in the phenological stages (V3, V5 and V7). As for the insect population (Coccinélidos, Nabis capsifonnes, Zelus nugar, Metacanthus tenellus, Chrisoperla externa y Arácnidos), was found that treatment with the mixture of more Dethomil Troy insecticides to beneficia! insect population most affected evaluated; and no significant statistical difference in performance.